DESIGN AND ANALYSIS OF THERMAL TECHNOLOGIES- BASED COMMUNAL WASTE PROCESSING FACILITY - Ahmad Syauqi, Hafiz
To solve the overcapacity problem in landfill, government has started a program to build a communal waste processing facility called Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS3R). However, after conducted some observation to typical TPS3R, it was known that TPS3R still has a lot of drawbacks. One way to solve the problems is by replacing the conventional waste processing system by using thermal-based technologies that has higher processing percentage and rate. Therefore, this final project discusses the design process of thermal technology-based waste processing facility is to replace the conventional one. Seven design alternatives were compared to each other by Analytical Hierarchy Process (AHP) according to several parameters, such as: the processed waste percentages, specific processing capacity, energy sustainability, Global Warming Potential (GWP), and daily cash flow. The design with highest value in AHP matrix was selected as the recommended design system to be applied. The financial feasibility and sensitivity analysis of the selected design was also conducted to study its implementation feasibility. The analyzed financial parameters are Net Present Value (NPV), Discounted Payback Period (DPBP), and Internal Rate of Return (IRR) Based on the determined parameters, design alternative that combined sorting, hydrothermal, pyrolysis, incineration, and landfilling processes was the most recommended system. This design excelled other alternatives in processed waste percentages, daily cash flow, and the GWP; though, it lacked in the specific processing capacity and the energy sustainability. The value of NPV, DPBP, and IRR were IDR 4,359,908,623, 3 years and 4 months, and 34.5%, respectively, which made it feasible to be implemented.